Monocyte/high-density lipoprotein cholesterol, neutrophil/high-density lipoprotein cholesterol, and lymphocyte/high-density lipoprotein cholesterol ratios as new inflammatory markers in rosacea - Bülent Nuri Kalaycı (Galenos Publishing House, 2023)
Background and Design: Rosacea is a chronic inflammatory skin disease. The monocyte/high-density lipoprotein (HDL) cholesterol ratio (MHR), neutrophil/HDL cholesterol ratio (NHR), and lymphocyte/HDL cholesterol ratio (LHR) are new inflammatory parameters associated with inflammatory diseases. This study aimed to compare MHR, NHR, and LHR between patients with rosacea and healthy controls and determine the relationship of these parameters with disease severity. Materials and Methods: The study retrospectively included 82 patients who presented to our hospital with rosacea and 82 healthy controls. The MHR, NHR, and LHR of the patient and control groups were calculated. Patients were divided into groups according to the clinical subtypes, disease severity, and presence of Demodex mites. Results: Of the 82 patients included in the study, 62 (75.6%) were female and 20 (24.4%) were male, and their mean age was 41.95+-1.2 (22-65.43) years. The mean MHR values of the rosacea and control groups were 0.01+-0.005 and 0.009+-0.003, respectively, and the difference was statistically significant (p=0.01). The mean NHR values of the rosacea and control groups were 0.10+-0.05 and 0.08+-0.02, respectively, and the difference was statistically significant (p=0.04). The mean LHR values of the rosacea and control groups were 0.05+-0.02 and 0.04+-0.01, respectively, indicating no statistically significant difference (p>0.05). For the prediction of patients with rosacea, the cut-off MHR was calculated as 0.009 (67% sensitivity and 60% specificity) and that of NHR was 0.08 (64% sensitivity and 60% specificity). Conclusion: The results reveal that MHR and NHR parameters can be used as indicators of systemic inflammation in patients with rosacea.